Hindi aur Hindu-Muslim sanskrtik ekta - Singh, Ramphal (Dilli : Rajeś Prakaśan, 2010)
Study on the contribution of Muslim authors in Hindi literature and cultural history of Hindu-Muslim unity in India
Na hindskom.
Keywords: hindska književnost - muslimanski autori; Muslimani u Indiji; indijska kulturna povijest - doprinos Muslimana; Indija - etnički odnosi